Risk and trust using mHealth application - Hamdan Hamdan; Deden Kurniawan; Erna Sofriana Imaningsih; Amzad Samudro (Jurnal Manajemen dan Pemasaran Jasa, 2021)
Since the COVID-19 pandemic, the increase in active users of the mHealth application as a doctor’s teleconsultation transaction, drug purchases, and other test services, especially the COVID-19 test service on a drive-thru basis, has increased significantly. The trend of health app user behavior indicates the importance of health. To reveal this phenomenon, the approach used is descriptive-quantitative with SEM-PLS analysis method using SmartPLS software. This finding is to make an important contribution for stakeholders that the main consideration factors for consumers intending to use mHealth application are risk and trust. The consequences for high risk are not proportional to the trust in the application, but when the trust as a mediator can lead to a positive attitude from consumers on the risk that will be accepted as a concrete action to use it. In the end, consumers’ strong trust reflects their behavior towards their intention to use the mHealth application.